Can bitcoin serve as a reliable safe haven? Amid uncertainty and volatility - Nugraha, Pazri; Saptutyningsih, Endah; Nguyen, Tran Thai Ha; Darsono, Susilo Nur AJi Cokro (Journal of Accounting and Investment, 2026)
Research aims: This study examines whether Bitcoin can serve as a safe-haven asset amid global market uncertainty during the 2022–2025 period, characterized by geopolitical tensions, post-pandemic inflation, and heightened financial volatility.Design/Methodology/Approach: The study employs a quantitative approach using daily data on Bitcoin, gold, oil, the S&P 500 index, and the Volatility Index (VIX) from January 2022 to June 2025. All variables are transformed into logarithmic returns and analyzed using an ARCH model to capture time-varying volatility and assess the influence of global market factors on Bitcoin returns..Research findings: The empirical results indicate that the VIX has a statistically significant negative effect on Bitcoin returns, implying that rising global uncertainty weakens rather than strengthens Bitcoin’s value. The S&P 500 exerts a significant positive influence, showing that Bitcoin moves pro-cyclically with equity markets and behaves like a risky asset. Oil prices have no significant impact, while gold returns exhibit a significant but unstable co-movement, lacking consistent value preservation. Overall, these findings reject Bitcoin’s safe-haven role and characterize it as a speculative digital asset with high sensitivity to stock market dynamics.Theoretical contribution/Originality: This study contributes to the safe-haven and digital finance literature by providing recent empirical evidence that distinguishes Bitcoin from genuine safe-haven assets. Grounded in formal safe-haven theory and volatility dynamics, it challenges the “digital gold” narrative and clarifies the boundary between high-risk digital assets and traditional safe havens.Practitioner/Policy implication: For investors, the results of this study confirm the need for caution in treating Bitcoin as a portfolio diversification instrument, as its behavior is more like that of a risky asset than a hedge asset. For Policymakers and regulators, these results show the importance of public education regarding Bitcoin's volatility risks and its limitations as a safe haven.